বানী বিচিত্রা - (:unkn) unknown (Banee Prakashani)
Approved by the Board of Secondary Education Assam, this is a text book of Bengali Grammar for classes VIII to X standard.
Banee Bichitra, Class VIII- X
Keywords: Bengali; Bengali Grammar; Bengali; Bengali